Fundamentos do pensamento socioeconômico do Papa Francisco - Rocha, Renato Tarcísio de Moraes (Revista Eclesiástica Brasileira, 2023)
No presente artigo, o autor propõe, com o auxílio do conhecido método indutivo, uma análise sistemática do ensinamento socioeconômico do Papa Francisco. Em seu conjunto, a reflexão possibilita compreender qual é a apreciação (ver), o discernimento (julgar) e as propostas (agir) do atual pontífice acerca da questão econômica. Se, de um lado, o aludido ensinamento recobra e evidencia importantes elementos do tradicional Magistério Social da Igreja, de outro, o modo como Francisco os pensa, enfatiza e representa uma contribuição original para a necessária transição da idolatria do mercado a uma economia com rosto humano. Abstract: in this article, the author proposes, with the help of the established inductive method, a systematic analysis of the socio-economic teachings of Pope Francis. As a whole, the reflection makes it possible for one to understand the appreciation (to see), the discernment (to judge) and the proposals (to act) of the current pontiff about the economic question. If, on the one hand, the aforementioned teaching recovers and highlights the important elements of the traditional Social Magisterium of the Church, on the other hand, the way Francis thinks, emphasizes and reproposes them represents an original contribution for a necessary transition from the idolatry of the market to an economy with a human face. Keywords: Pope Francis; Social moral; Economy; Market.